2011
DOI: 10.1128/cvi.05082-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antigenic Targets for Immunodetection of Balamuthia mandrillaris Infection

Abstract: The free-living amoeba Balamuthia mandrillaris causes granulomatous amoebic encephalitis (GAE) in humans. Rapid identification of balamuthiasis is critical for effective therapeutic intervention and case management. In the present study we identified target antigens for the development of a serological assay for B. mandrillaris infection. We demonstrated by silver staining that protein profiles for all eight isolates of B. mandrillaris, independent of human or animal origin or geographic origin, appeared to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Studies of patients with encephalitis have found that IFA and ELISA testing appear to be relatively specific for B. mandrillaris infection, suggesting that they are good markers for exposure (Kucerova et al 2011; Schuster et al 2001; Schuster et al 2008). Further, our findings confirm those from other studies showing that infections with other parasites, including infections with other amebae, do not yield false positives on B. mandrillaris antibody testing (Kiderlen et al 2009; Kiderlen et al 2010; Schuster et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of patients with encephalitis have found that IFA and ELISA testing appear to be relatively specific for B. mandrillaris infection, suggesting that they are good markers for exposure (Kucerova et al 2011; Schuster et al 2001; Schuster et al 2008). Further, our findings confirm those from other studies showing that infections with other parasites, including infections with other amebae, do not yield false positives on B. mandrillaris antibody testing (Kiderlen et al 2009; Kiderlen et al 2010; Schuster et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…To grow amebae for antibody testing, we cultured B. mandrillaris (CDC:V619; isolated from the CSF of a GAE patient from Mississippi in 2010) on monolayers of monkey kidney (E6) cells as described before (Kucerova et al 2011) and harvested cultures after they cleared the monolayer by ingesting all of the tissue culture cells. We then chilled the flasks on ice for 2 to 5 minutes, shook them to dislodge the amebae, and washed them three times in Hanks’ balanced salt solution (HBSS; Gibco catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…The HLF cell cultures were sub-cultured periodically and amebae were harvested and stored at −80°C. The amebae stored at −80°C were thawed and disrupted and the resulting protein antigens were subjected to SDS-PAGE (Kucerova et al 2011). Separated proteins were silver stained and compared with protein profiles of other isolates (Kucerova et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The amebae stored at −80°C were thawed and disrupted and the resulting protein antigens were subjected to SDS-PAGE (Kucerova et al 2011). Separated proteins were silver stained and compared with protein profiles of other isolates (Kucerova et al 2011). Real-time PCR (Qvarnstrom et al 2006) was performed on DNA from brain tissue, CSF and cultured amebae, extracted using the DNeasy tissue and blood kit (QIAGEN).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation